Managerial Competencies, Self Efficacy, and Job Performance : A Path Analytic Approach - Lakshminarayanan, Sethumadhavan; Pai, Yogesh P.; Ramaprasad, Badrinarayan Srirangam (Prabandhan: Indian Journal of Management, 2016)
There is no dearth of studies establishing the relationship between managerial competencies and job performance across sectors. However, the manufacturing sector in India has received less attention from the researchers. Furthermore, previous studies provided fewer insights into ’how’ managerial competencies affect job performance. This study precisely aimed to fill these observed gaps by first focusing on middle managers from the manufacturing sector in India, and secondly, by expounding the role of proximal variables like self-efficacy in understanding the relationship between managerial competencies and job performance. The results from this study indicated that ’self-management’ competency exerted the maximum influence on job performance followed by ’relationship management’ and ’analytical skills’. Self-efficacy was found to partially mediate the relationship between competencies and job performance. Also, the results wielded strong evidence that managerial competencies and self-efficacy together are relatively stronger in predicting job performance than either predictor by itself. Furthermore, the study provides insights into the research and managerial implications of such findings.